Analisis Perkembangan Produksi Perikanan Budidaya Di Kabupaten Rokan Hulu Provinsi Riau - Bathara, Lamun; Hamid, Hamdi; ', Rinaldi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
The Research on Analysis of Aquaculture Production Development wasconducted in 31 May – 16 June 2014 at Rokan Hulu Regency of Riau Province.The aims of the study were to determine the aquaculture resource potentialthrough the production development analysis, includes the effect of theaquaculture production and also production estimate for the next five years. Themethod used in this study is a Survey Research Development to view theproduction progress each year to support district development.The result showed that the progress of aquaculture production increasedannually with average of 25% per year, and the impact of aquaculture toproduction about 80,8 %, as well as production estimate for 5 years.Keywords : Development, Production, Rokan Hulu district